Cost-consequence analysis of 18F-fluciclovine for the staging of recurrent prostate cancer - Ivar S Jensen; Joanne Hathway; Philip Cyr; David Gauden; Peter Gardiner (Taylor & Francis Group, 2020)
Background: Current detection methodologies are often unable to identify the location and extent of recurrent prostate cancer (PCa) leading potentially to 'futile' local therapies in the presence of metastatic disease. The use of 18 F-fluciclovine PET/CT may lead to better patient management. Objective: The aim of this study was to quantify the economic impact and cost-consequence of using 18 F-fluciclovine PET/CT in PCa recurrence. Study design: A decision analytic model based on recurrent PCa imaging guidelines. Setting: US hospital. Participants: PCa patients experiencing biochemical recurrence. Intervention: 18 F-fluciclovine PET/CT was compared to conventional imaging. Main outcome measure: Budget impact, correct diagnoses, futile treatments, and cost-consequence (cost per correct diagnosis) Results: For a hypothetical hospital serving 500,000 individuals, the model showed the use of 18 F-fluciclovine reduced 'futile' therapies by 19.2%. Re-imaging costs were reduced by 40.2% ($8.2 million); however, when assuming diagnostic and staging costs only, the total costs increased from $31.2 to $34.6 million (10.9%), driven by 18 F-fluciclovine imaging agent and procedure costs. The cost per 'correct' diagnosis declined $30,673 (46.8%). When including subsequent 5-year patient management, the cost per 'correct' diagnosis declined $410,206 (49.2%). Conclusion: 18 F-fluciclovine PET/CT imaging may improve the clinical management of men with recurrent PCa with minimal increase in healthcare spending.